2021
DOI: 10.3390/rs13173444
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network with a Learnable Spatial Activation Function for SAR Image Despeckling and Forest Image Analysis

Abstract: Synthetic aperture radar (SAR) images are often disturbed by speckle noise, making SAR image interpretation tasks more difficult. Therefore, speckle suppression becomes a pre-processing step. In recent years, approaches based on convolutional neural network (CNN) achieved good results in synthetic aperture radar (SAR) images despeckling. However, these CNN-based SAR images despeckling approaches usually require large computational resources, especially in the case of huge training data. In this paper, we propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…These rules determine the ground and satellite information of the merged SM. In recent decades, experiments have demonstrated that CNN-based deep learning methods are reliable for predicting SM using multisource data [46][47][48]63]. Recently, CNNs have been used successfully for SM estimations based on Sentinel multisource data [49].…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…These rules determine the ground and satellite information of the merged SM. In recent decades, experiments have demonstrated that CNN-based deep learning methods are reliable for predicting SM using multisource data [46][47][48]63]. Recently, CNNs have been used successfully for SM estimations based on Sentinel multisource data [49].…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…The long short-term memory (LSTM) model (which represents the state-of-the-art recurrent cell in many fields) was first proposed in 1997 [37][38][39][40][41][42][43]. CNNs were originally designed to resolve image classification problems and they have been applied effectively for remote-sensing-based image classification [44][45][46][47][48]. Recently, CNNs have been successfully used for soil moisture estimations based on Sentinel multi-source data [49].…”
Section: Introductionmentioning
confidence: 99%